Analisis Kualitas Pelayanan dan Kepercayaan Konsumen Bus Rapid Trans Semarang di masa Pandemi Covid-19 - Agung Sedayu; Windya Ardani Salsabilla (JURNAL EKUIVALENSI, 2021)
The city of Semarang as the capital city of Central Java Province is included in the category of a metropolitan city because it has a population of more than 1.5 million people, so the level of activity and mobility of the community is increasing. The Semarang City Government through the Semarang City Transportation Service has succeeded in developing the Trans Semarang Rapid Transit Bus as a mass public transportation program that is more comfortable, safe, fast, cheap, and mass in nature. However, in 2020 the Covid-19 pandemic emerged which had a very large impact, even though the number of passengers decreased during the Covid-19 pandemic, the Semarang BRT continued to serve passengers and continue to provide the best service for passengers by implementing health protocols as recommended by the government. The population of this study was BRT Semarang users with a sample of 100 respondents. By using the Kano model approach, the researcher uses 31 service attributes which are composed of service quality, trust, and customer satisfaction variables. From the results of this study, 26 attributes fall into the Attractive category or pleasure attribute (A) and 5 attributes fall into the One dimensional category or the expected attribute (O). so that BRT Semarang must improve the quality of service better by evaluating employee performance and making improvements and improving service strategies, providing safe service quality by implementing health protocols for all consumer characteristics, especially during this Covid-19 pandemic.